International Journal of Economics and Accounting's introducing the classics: Abraham Briloff's 'The gap in GAAP'. (10th November 2010) - Sy, Aida; Tinker, Tony
The accounting classics series in the International Journal of Economics and Accounting is an important strand in this journal's policy of bringing a critical understanding of auditing and financial reporting. This journal is only interested in the technocratic regression and market studies research, if authors display a degree of critical self-reflection. The tacit ideological thrust of mainstream market studies research is an affirmation of the market and its capacity to deliver economic and social equilibrium results. Market studies publications rarely wear this ideology openly on its sleeve; rather their delivery is slick – sticking to 'the facts' allowing the data to 'speak for itself'. The applause for the market is implicit and its efficacy is taken as 'self-evident' – that's the successful advanced economies work. Of course, that's all changed; we are in deep trouble, and urgently need to revisit Briloff and the lessons he brings us (Cooper, 2008).